Strategi Komunikasi Interpersonal Guru Dalam Menanamkan Nilai-Nilai Islam Pada Anak Autisme - Hikmawati Hikmawati; Nur Kholifah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study is entitled Teachers 'Interpersonal Communication Strategies in Instilling Islamic Values in Autistic Children aims to determine how teachers' interpersonal communication strategies in instilling Islamic values in children with autism, what factors affect its success and obstacles.This study uses a qualitative approach with descriptive methods. The paradigm used is constructivism. The theories used are self disclosure by Sidney Marshall Jourard, symbolic interactionism by George Herbert Mead and Blumer, and Gerald Miller's Interpersonal Communication Strategy. students, using media, giving examples of actions, special treatment, habituation, as well as assertiveness. Factors of success that teachers do is by being a creative teacher, the existence of supportive facilities, patience, and cooperation between the school, parents, community. The obstacles are that autistic students have poor communication skills, are easily upset and difficult to communicate, have a mood that is easily changed and difficult to understand their speech, often engrossed in their own world, like to attack, and seek attention. How to deal with it patiently, straighten and direct better, give space to students, adjust conditions, be firm, and dare to stop students.